I can be a physicist - Sipiera, Paul P. (Chicago : Childrens Press, 1991)
Describes, in simple text and illustrations, physics and the work of a physicist.
School Library Journal.
4.9
4.9
K-3.
K-3
Keywords: Physics -- Vocational guidance -- Juvenile literature; Occupations; Physicists; Physics; Occupations; Physicists; Physics